ANALISIS STRATEGI ORGANISASI DAN IMPLIKASINYA TERHADAP KINERJA: TINJAUAN LITERATUR - Cindy Aprilia Gultom; Kurnia Estuningtyas (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Strategic management is an essential approach for organizations in responding to increasingly dynamic and competitive environments. Organizational strategy serves as a guideline for achieving long-term objectives and improving organizational performance sustainably. However, previous studies reveal inconsistent findings regarding the relationship between organizational strategy and performance, particularly in terms of strategic approaches and organizational contexts. Therefore, a comprehensive synthesis of existing literature is required. This study aims to analyze organizational strategies and their implications for organizational performance through a literature review approach. The research employs a Systematic Literature Review (SLR) method by examining scientific journal articles published between 2020 and 2025. The article selection process was conducted systematically through identification, screening, eligibility assessment, and synthesis stages, resulting in eight primary articles relevant to the research focus. The findings indicate that organizational strategy has a significant influence on organizational performance. The most frequently discussed strategies in the literature include strategic planning, strategy implementation, strategic leadership, and human resource management strategies. Furthermore, the results suggest that organizational performance can be optimized when strategies are implemented in an integrated manner and supported by effective leadership and proper resource management. This study contributes conceptually by providing an integrated synthesis of organizational strategy and performance and is expected to serve as a reference for academics and practitioners in developing and implementing strategic management practices.